Si-ULIN (Ready to Childbirth) as Pocket Book to Improve Knowledge and Attitude of Pregnant Women in Mantang Island - Rahmadona Rahmadona; Utami Dewi (Aloha International Journal of Health Advancement (AIJHA), 2021)
In Indonesia, preparation for childbirth is generally obtained through classes for pregnant women which are routinely held by the puskesmas or midwife clinic, but for the archipelago sometimes the presence of pregnant women is constrained by geographical conditions, limited transportation facilities, weather conditions and currently the Covid-19 pandemic situation. This condition can be overcome by presenting educational media for childbirth preparation. The purpose of this study was to analyze the effect of health education using “Si-ULIN” (Ready to Childbirth) pocket book on the knowledge and attitudes of pregnant women on Mantang Island, Bintan Regency, Riau Archipelago Province. This type of research was a quasi-experimental with one group pretest posttest design. The study was conducted in October 2020, involving 36 third trimester pregnant women on Mantang Island, who were selected using a purposive sampling technique. Data about knowledge and attitudes were collected through filling out a questionnaire, then analyzed using a paired sample t-test. The results showed that the average knowledge of pregnant women increased by 19.83 and the average attitude increased by 17.53 after being treated in the form of health education using the "Si-ULIN" pocket book. The p-value for differences in knowledge and attitudes before and after treatment were 0.000. This study concludes that “Si-ULIN” pocket book is effective in increasing the knowledge and attitudes of pregnant women about preparation for childbirth. It is hoped that all pregnant women with limited access to attend classes for pregnant women can use the “Si-ULIN” pocket book as an educational medium for preparation for childbirth. Keywords: pregnant women; pocket book “Si-ULIN”; knowledge; attitude